The Role of Digital Readiness and AI Skills in MSME Business Sustainability in the Era of Digital Transformation - Santosa, Muhammad Hery; Setiawan, Muhammad Akbar (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2026)
Digital transformation and the adoption of Artificial Intelligence (AI) are becoming increasingly urgent for Micro, Small, and Medium Enterprises (MSMEs) to maintain competitiveness in a technology-driven economy. This study aims to examine a structural model that explains the influence of digital readiness, AI skills, and policy support on MSME business sustainability using the Partial Least Squares–Structural Equation Modeling (PLS-SEM) approach. Data were collected from 155 MSMEs in Purbalingga Regency engaged in the culinary, fashion, and handicraft sectors. The findings show that digital readiness has a significant effect on AI skills and business sustainability, whereas AI skills and policy support do not yet demonstrate a significant influence on business sustainability. These results highlight the importance of digital readiness as the primary foundation for adapting AI-based marketing strategies, as well as the need to strengthen AI skills and provide more targeted policy support to optimize the benefits of technology. This study contributes practically by offering recommendations for MSMEs, support institutions, and policymakers, and theoretically by reinforcing the concept of Dynamic Capability in the context of AI adoption.